Challenges for Bilingual education at the junior secondary level of education in Sri Lanka: Student and teacher perspectives - Subhashinie Wijesundera; Sakunthala Yatigammana; Prasad Sethunga (The Open University of Sri Lanka, 2021)
The purpose of this qualitative case study is to understand the challenges for implementing Bilingual Education (BE) at the junior secondary level of education in Sri Lanka from the perspective of students and teachers. Six bilingual teachers and 30 students from Grades 6 and 8 of a selected school participated in the study. Focus Group Interviews (FGI) with the students and semi-structured interviews with the teachers were used to generate data. It has emerged in the analysis that both teachers and students face many challenges and issues in teaching, learning and assessments in their classrooms mainly due to lack of adequate and appropriate physical and human resources and the lack of necessary support from school and other educational authorities. Teachers with limited experience and training in BE had to face many difficulties in teaching and assessment of students due to the lack of sufficientL2 proficiency among their learners. Students, in turn, face challenges in learning and assessments due to the lack of necessary basic skills in L2 and support from their teachers, peers and home environments as well as self-learning skills. In conclusion, the authors argue that since BE is beneficial to both individuals and society, it needs to be expanded and further developed to enhance equity, inclusivity, and quality of education and capacity for lifelong learning among learners. Moreover, for successful implementation of BE, teachers and students should be adequately supported through a 'try level engagement' approach to education reforms.